Digital Transformation in Supply Chain Management: Artificial Intelligence (AI) and Machine Learning (ML) as Catalysts for Value Creation - Singh, Pratyush Kumar (International Journal of Supply Chain Management, 2023)
In the rapidly evolving landscape of supply chain management (SCM), digital transformation has become a cornerstone for achieving competitive advantage. This paper explores the pivotal role of Artificial Intelligence (AI) and Machine Learning (ML) as catalysts in this transformation, driving significant value creation across various facets of SCM. Through a comprehensive literature review, including an analysis of 12 key papers, this study examines the integration of AI and ML in enhancing supply chain operations, from predictive analytics in demand forecasting to real-time decision-making in logistics and inventory management. The findings highlight the transformative impact of these technologies in optimizing efficiency, reducing costs, and improving overall supply chain resilience. The paper also addresses the challenges and ethical considerations inherent in implementing AI and ML, such as data privacy and workforce implications. Concluding with a look towards the future, this study underscores the growing importance of AI and ML in shaping the next generation of SCM practices. This research not only contributes to the academic discourse on digital supply chain transformation but also offers practical insights for industry professionals navigating this digital shift.